A new look at early exposure to the flavors of the available vegetables as foundational mechanism of vegetable consumption habits and recipes of vegetables-based dishes. Issue 5 (9th March 2021) - Domínguez, Paloma Rohlfs
Abstract: The flavor of the maternal diet is transferred to women's amniotic fluid and breast milk, so that the amniotic fluid and breast milk become natural transmitters of flavor-related information developing babies are exposed to at early stages of development. We aimed to review the available evidence regarding the impact of early exposure to flavor on child vegetable intake, and to discuss for the first time possible effects of availability or unavailability of particular vegetables because of geographic reasons on these exposures, a variable that has been forgotten in the literature. We have focused on studies that have examined the association of prenatal and early postnatal -at breastfeeding- exposures to vegetable-related flavors with vegetable consumption in children. We have identified that this particular kind of exposures may lead to increases in children's acceptance, liking of and preference for the vegetables. Especially novel has been to identify that these effects might be modulated not only by the particular flavor of the vegetable -bitter vs. sweet- and the time of exposure -prenatal vs. breastfeeding- but also by vegetable availability because of geographic reasons of the place of residence of the mother, a variable that should be taken into account in future research. This would give rise to a new research line aimed at solving the mentioned gap. Finally, a theoretical model of cyclical processes that might explain the origin and perpetuation of transmission of particular patterns of vegetable consumption and vegetables-composed dishes over time in a given population is also included here as another new contribution.